Developmental incompetence in selected and naturally occurring Trypanosoma isolates - Oldrieve, Guy R. (The University of Edinburgh, 2023)
Trypanosoma brucei has two distinct life stages in its mammalian host. The proliferative ‘slender’ form develops into a cell-cycle arrested ‘stumpy’ form at high parasite density. This transition occurs in a density-dependent quorum sensing (QS) like process, for which critical molecular regulators have been identified. Naturally occurring T. brucei subspecies (T. b. evansi and T. b. equiperdum) have reduced ability to generate the stumpy form and are described as ‘monomorphic’. Utilising whole genome sequences of 41 naturally occurring monomorphic isolates, we corroborate previous studies in identifying at least four independent monomorphic T. brucei clades. Mutations in six genes were then explored for their contribution to monomorphism. The orthologous gene sequences were synthesised and used to replace wild-type alleles, via CRISPR-Cas9, in developmentally competent T. brucei. The replacement of two targets with the monomorphic mutant sequence reduced the ability to generate stumpy forms in developmentally competent cells. Furthermore, we identified mutations associated with cell proliferation and motility phenotypes. We also selected monomorphic cell lines from a pleomorphic population and confirmed significant downregulation of transcripts of a developmental regulator, ZC3H20, during the progression to monomorphism. In vitro overexpression of ZC3H20 in the selected monomorphic cells restored pleomorphism. Independently selected monomorphic lines generated in vitro were also found to show consistently altered regulation of several transcripts, hinting that the initial steps to monomorphism may share similarities in discrete populations. We suggest that, in the field, monomorphism develops on a spectrum via modifications to the regulation of key QS genes, which can be reversed in the first instance. As the scale tips towards developmental incompetence, mutations accrue in key QS genes which lock the parasites in a monomorphic phenotype. This provides insight into the molecular control of the QS process and possible diagnostic tools to anticipate increased virulence in the field.
Keywords: Developmental incompetence; trypanosoma isolates; naturally occurring trypanosoma isolates; Trypanosoma brucei; quorum sensing (QS); T. b. evansi; T. b. equiperdum; orthologous gene sequences; CRISPR-Cas9; ZC3H20